2016
DOI: 10.1249/mss.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

Mental Fatigue Impairs Soccer-Specific Physical and Technical Performance

Abstract: Mental fatigue impairs soccer-specific running, passing, and shooting performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
358
4
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(415 citation statements)
references
References 39 publications
26
358
4
27
Order By: Relevance
“…Central fatigue could also be an inherent factor in the game, being important towards the end of the game and linked to the deterioration in physical capacity. It is obvious that central fatigue deteriorates technical performance [45], accuracy and decision-making speed [46], but there is no scientific consensus regarding what is the effect of central fatigue on physical performance [4,45,47]. As a consequence, more research is needed to clarify the impact of central fatigue on soccer-specific physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Central fatigue could also be an inherent factor in the game, being important towards the end of the game and linked to the deterioration in physical capacity. It is obvious that central fatigue deteriorates technical performance [45], accuracy and decision-making speed [46], but there is no scientific consensus regarding what is the effect of central fatigue on physical performance [4,45,47]. As a consequence, more research is needed to clarify the impact of central fatigue on soccer-specific physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…sleep restriction) may lead to increased fatigue experiences [7,12,13] and an increased injury risk [14]. For example, it has been shown that lowering psychological fitness by performing a cognitively demanding task leads to increased fatigue levels during subsequent soccer-specific physical exercise [13].…”
Section: Introductionmentioning
confidence: 99%
“…De facto, é esperado (embora não obrigatório) que o estudante-treinador seja responsável pela organização e monotorização das tarefas instrucionais durante a aula, bem como pela orientação geral da sua equipa (41) . Não obstante, à exceção do estudo de Wallhead e O'Sullivan (44) , até ao momento, esta análise era quase inexistente. .…”
Section: Dinâmicas Operantes No Seio Das Equipasunclassified
“…Como as situações esportivas exigem dos jogadores respostas rápidas e efetivas (16,60) , o melhor desenvolvimento da cognição ajudará a minimizar as consequências do desgaste cognitivo sobre as respostas físicas e motoras (8,44,54,59) .…”
Section: Avaliações In Vivounclassified
See 1 more Smart Citation